Pengaruh Kepemimpinan Transaksional dan Motivasi Kerja Terhadap Kinerja Karyawan Melalui Komitmen Organisasional Di PT Persada Sejati Jakarta - Melkianus Albin Tabun; Marcelina W Putri; Stanley Tulus (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
This study aims to determine the effect of transactional leadership and work motivation on employee performance through organizational commitment. This research was conducted on 261 technician employees of First Media PT. Rizki Persada Sejati in Jakarta. The data was collected by distributing questionnaires via google form containing 65 questions with a Likert scale of 1 - 5 based on the simple random sampling method. Data were analyzed using path analysis method with linear regression approach. The results showed that transactional leadership and work motivation have a positive and significant effect on employee performance and organizational commitment. Meanwhile, based on the results of the path analysis carried out, the results show that the variable organizational commitment does not mediate the effect of transactional leadership and work motivation on employee performance because the transactional leadership variable has a direct effect coefficient value of 0.175 which is greater than the indirect effect coefficient value - 0.017, as well as work motivation. has a direct effect coefficient value of 0.652 greater than the indirect effect coefficient value of 0.209.